The Notion Of “Premium Friday” And “Shining Monday”: An Effective Initiative To Eliminate Employees Related Issues - Ansari, Zaid Ahmad; Ali, Wasif (Advances in Social Sciences Research Journal, 2019)
The main objective of this study was to find out how “Premium Friday” and “Shining Monday” can be helpful in minimizing the employee related issues such Employee Motivation, Turnover, Stress, Absenteeism, Conflict, Awful Performance, and Work Life Balance. Paper is theoretical in nature and concepts have been described by relevant literature. The main outcome of the paper showed that if “Premium Friday” and “Shining Monday” programmes are implemented by management of various concerns in appropriate way, it may produce positive results with regard to employee related issues and it could be effective in eliminating employee problems, which in turn would increase the employee efficiency and productivity.